Effect of canola processing by bacteria, fungi, and enzyme on the intestine traits and blood metabolites of broiler breeder hens - DOLATIFARD, AMIR; JAFARI, MOHAMMAD ALI (The Indian Journal of Animal Sciences, 2021)
Anti-nutritional factors of canola meal are reduced by processing. The purpose of the current research was to study the canola processing effect on the intestinal traits and blood metabolites of broiler breeder hens. Broiler breeder hens (450) were reared for 12 weeks. A completely randomized design was used with 6 treatments (unprocessed, processed by Lactobacillus plantarum, Bacillus subtilis, Aspergillus oryzae, Neurospora cytophilla, and Alkalase enzyme) and 5 replications. The LS-means procedure of SAS statistical software was used for the analysis of the data. The treatments’ effect was significant on all blood metabolites. Process methods were increased glucose concentration and HDL. The effect of processing methods was significant on caecum, jejunum, and duodenum. The use of experimental treatments increased the weight of the small intestine (duodenum and jejunum) and decreased caecum weight. The processing of canola meal increased the length of the villi and decreased the depth of the crypt of jejunum. The canola process improved its digestibility. Protein quality, fatty acid profile, and antimicrobial properties were improved. The processed canola used by the bird improves its traits and can be recommended to use in the ration.